Proses Pelaksanaan Roya Partial Pada Kantor Notaris - Saputra, Gilang Bella; Dedy Priyanto, I Made (Acta Comitas : Jurnal Hukum Kenotariatan, 2020)
Roya Partial is a new legal institution formed, by providing an alternative settlement of repayment on a credit basis by paying off a portion of the credit that goes by pulling some of its collateral. “Article 2 of the Law No. 4-year 1996 on land rights and objects relating to the land”, giving gaps in the performance of Roya Partial. Whereas article 1163 Civil Code states the rights of liabilities (mortgages) are not indivisible but bind all parts of the goods/moving objects. This can actually lead to a conflict of norms against both regulations. Based on that, formulated 2 problems 1) What is the legal basis of the implementation of a partial Roya, (2) How to process the implementation of Roya Partial in notary Office, the purpose of this research is to know the legal basis in the implementation of a partial roya and to know the process of implementing Roya Partial in notary office.  The legal research method used is a normative legal research method of using a statutory approach, and a conceptual approach. Right to land that can be burdened by article 4 UUHT Jo article 25, 33, 39 UUPA namely: property rights, business rights, building rights, rights, houses and property rights in the unit and there are several procedures regarding the deletion of liabilities from the settlement to the execution of the force, then the method of implementation of a partial Roya notary office.